A LOOK AT PUBLISHED INTERIM REPORTS. - Taylor, Robert G. (The Accounting Review, 1965)
Abstract This article presents the results of a recent study of a financial report that has been virtually ignored by most accountants. This report, the published interim report, has been strongly advocated by the U.S. Securities & Exchange Commission, the New York Stock Exchange and various other stock exchanges. In addition, it has been strongly demanded by financial analysts as a necessary part of systematic, orderly flows of financial information. In spite of the increased demand for such reports, many accountants of all types, both industrial, professional and academic, have either ignored or opposed them. This paper is also intended to remedy that situation somewhat. As one know, accountants and financial reports are completely interrelated. Communication of financial information is the essence of accounting. Financial reports are the obvious media of this communication and since published interim reports have become a significant part of the financial reporting practices of many corporations, accountants must take cognizance of them.